2023
DOI: 10.3390/foods12112168
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Snacks Manufactured from Andean Tubers and Tuberous Root Flours: Microwave Expansion Kinetics and Characterization

Abstract: Andean tubers and tuberous roots have nutritional and medicinal properties transferred through ancestral generations. In this study, we aim to promote cultivation and consumption by developing a snack based on these crops. Corn grits were thoroughly mixed with sweet potato, mashua, and three varieties of oca flour (white, yellow, and red) in an 80:20 ratio, and a single-screw laboratory extruder was utilized to produce third-generation (3G) dried pellets. Microwave expansion was studied, and the dried 3G pelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
1
4
0
Order By: Relevance
“…In this study, OtY had the highest carotenoid value (4.74 mg βcarotene /100 g of sample) (p < 0.05); this value was also highest in the Tt sample, which corresponds to mashua root, reported as a crop with an essential carotenoids content [9,80]. The TC value in OtY in this study was 1.63 mg βcarotene /100 g, which is more that of a 3G yellow oca obtained in a previous study [38]. Furthermore, the values are greater than those reported by Campos [81], who studied 14 oca genotypes (0.2-0.25 mg βcarotene /100 g of sample).…”
Section: Bioactive Compoundssupporting
confidence: 52%
See 2 more Smart Citations
“…In this study, OtY had the highest carotenoid value (4.74 mg βcarotene /100 g of sample) (p < 0.05); this value was also highest in the Tt sample, which corresponds to mashua root, reported as a crop with an essential carotenoids content [9,80]. The TC value in OtY in this study was 1.63 mg βcarotene /100 g, which is more that of a 3G yellow oca obtained in a previous study [38]. Furthermore, the values are greater than those reported by Campos [81], who studied 14 oca genotypes (0.2-0.25 mg βcarotene /100 g of sample).…”
Section: Bioactive Compoundssupporting
confidence: 52%
“…The AC results showed that the highest value corresponds to the OtY snack; however, there was a slight difference with the Tt snack ( p < 0.05). This is important because mashua eventually showed the best antioxidant activity of the Andean crops studied here and reported in the literature [ 10 , 38 , 87 ]. In contrast, Ce snacks had the lowest AC ( p < 0.05) between Andean crops; Ce was higher than C. The AC is attributable to the phenolic compounds, flavonoids, carotenes, and vitamin C, which are reported to be part of these roots [ 88 ].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Fresh-peeled slices (2 mm) were used to determine the initial water content (x w ). This determination was carried out in a Vaciotem vacuum oven (J.P. Selecta, Barcelona, Spain) set to 103 • C for 48 h. The slices were dried via convection in an air drier (model CD 160, Gander Mountain, Saint Paul, MN, USA) at 65 • C for 8 h, with the air velocity (2 m s −1 ) kept constant [14]. The drying temperature was established based on preliminary tests and the results obtained in a study on similar roots grown in the same area (lower temperature for a long time/60 • C for 24 h) [15].…”
Section: Determination Of Drying Kineticsmentioning
confidence: 99%
“…However, it has been studied that using microwaves, in addition to avoiding the increase in fat content by not requiring oil, helps to better preserve the color, texture, and functional properties of the snacks compared to those under frying [2]. This reason may explain why recent studies have chosen microwaves as a method for the expansion of snacks from lentil and egg powder [3], beetroot by-products [4], blue corn, black bean, sweet chard [5], and Andean tuber and tuberous root flours [6].…”
Section: Introductionmentioning
confidence: 99%